Association between Community Ambulation Walking Patterns and Cognitive Function in Patients with Parkinson's Disease: Further Insights into Motor-Cognitive Links. (29th October 2015) - Weiss, Aner; Herman, Talia; Giladi, Nir; Hausdorff, Jeffrey M.
Abstract : Background . Cognitive function is generally evaluated based on testing in the clinic, but this may not always reflect real-life function. We tested whether parameters derived from long-term, continuous monitoring of gait are associated with cognitive function in patients with Parkinson's disease (PD). Methods . 107 patients with PD (age: 64.9 ± 9.3 yrs; UPDRS motor sum "off": 40.4 ± 13.2; 25.23% women) wore a 3D accelerometer on their lower back for 3 days. Computerized measures of global cognitive function, executive function, attention, and nonverbal memory were assessed. Three-day acceleration derived measures included cadence, variability, bilateral coordination, and dynamic postural control. Associations between the acceleration derived measures and cognitive function were determined. Results . Linear regression showed associations between vertical gait variability and cadence and between global cognitive score, attention, and executive function (p ≤ 0.048 ). Dynamic postural control was associated with global cognitive score and attention (p ≤ 0.027 ). Nonverbal memory was not associated with the acceleration-derived measures. Conclusions . These findings suggest that metrics derived from a 3-day worn body-fixed sensor reflect cognitive function, further supporting the idea that the gait pattern may be altered as cognition declines and that gait provides a window into cognitive function in patients with PD.